Pervasive compartment‐specific regulation of gene expression during homeostatic synaptic scaling. (16th August 2021) - Colameo, David; Rajman, Marek; Soutschek, Michael; Bicker, Silvia; von Ziegler, Lukas; Bohacek, Johannes; Winterer, Jochen; Germain, Pierre‐Luc; Dieterich, Christoph; Schratt, Gerhard
Abstract: Synaptic scaling is a form of homeostatic plasticity which allows neurons to adjust their action potential firing rate in response to chronic alterations in neural activity. Synaptic scaling requires profound changes in gene expression, but the relative contribution of local and cell‐wide mechanisms is controversial. Here we perform a comprehensive multi‐omics characterization of the somatic and process compartments of primary rat hippocampal neurons during synaptic scaling. We uncover both highly compartment‐specific and correlating changes in the neuronal transcriptome and proteome. Whereas downregulation of crucial regulators of neuronal excitability occurs primarily in the somatic compartment, structural components of excitatory postsynapses are mostly downregulated in processes. Local inhibition of protein synthesis in processes during scaling is confirmed for candidate synaptic proteins. Motif analysis further suggests an important role for trans‐acting post‐transcriptional regulators, including RNA‐binding proteins and microRNAs, in the local regulation of the corresponding mRNAs. Altogether, our study indicates that, during synaptic scaling, compartmentalized gene expression changes might co‐exist with neuron‐wide mechanisms to allow synaptic computation and homeostasis. Synopsis: Downscaling of excitatory synapses in response to high activity involves compartment‐specific changes in the neuron's transcriptome and proteome. This study supports the view that local gene regulation is important in both Hebbian and homeostatic forms of synaptic plasticity. Hippocampal neurons grown on filter insets allow to study activity‐dependent changes in gene expression at the compartment level. Different sets of genes are regulated in the somatic and process compartment of hippocampal neurons during synaptic downscaling. The inhibition of genes encoding for excitatory synaptic proteins during downscaling occurs preferentially in the process compartment. Motifs for RNA‐binding proteins and microRNAs are highly enriched in mRNAs specifically downregulated in the process compartment. Abstract : Downscaling of excitatory synapses in response to high activity involves compartment‐specific changes in the neuron's transcriptome and proteome. This study supports the view that local gene regulation is important in both Hebbian and homeostatic forms of synaptic plasticity.